Analysis of Opportunities for the Development of Electromobility of urban Transport on the Territory of Pila District - Gorzelańczyk, Piotr; Warnke, Filip (Olsztyn Economic Journal, 2024)
In the transportation industry, electromobility has become an indisputable trend that is not going to go away any time soon. According to analyses of the industry’s growth, all signs point to an increase in the number of electric automobiles, which will eventually supplant conventional combustion vehicles. One electric vehicle is now sold every 1,000 people in Poland, where they make up roughly 4.5% of total automobile sales. 20,253 units were sold in 2021, a 93% increase from the previous year (Elektromobilność…, 2022). The continued efforts of the world’s leading economies to cut greenhouse gas emissions, which are hastening climate change, are unquestionably a significant element supporting this course. The aim of this article is to analyse the potential for the development of electromobility in the urban transport sector in Piła County. However, the success of this analysis will be possible during a period of transition in a number of important spheres. On the basis of the analysis, it can be concluded that such a possibility exists, as cars and other vehicles powered by electricity are becoming an alternative to traditional combustion vehicles, also reducing emissions of pollutants harmful to the environment. On the other hand, however, there are public concerns about this possibility, due to fires in electric cars, among other things.